THE INFLUENCE OF ZAKAT UNDERSTANDING, TRANSPARENCY, AND ACCOUNTABILITY ON THE INTEREST OF MUZAKKI IN PAYING ZAKAT IN LAZISMU KEBUMEN REGENCY - Risa Irnawati; Siti Afidatul Khotijah; Siti Rokhaniyah (Universitas Tidar, 2024)
This research aims to analyze the influence of zakat understanding, transparency, and accountability on muzakki's interest in paying zakat at LazisMu Kebumen Regency. This research includes quantitative research which is used to determine interest in paying zakat. Data was collected in this research by distributing questionnaires to 100 muzakki using a non-probability sampling method with a purposive sampling technique. Data analysis was carried out using a multiple linear regression approach. The results of the analysis show that zakat understanding and accountability have a positive effect on muzakki’s interest in paying zakat in LazisMu Kebumen Regency. Meanwhile, transparency does not have a significant effect on muzakki’s interest in paying zakat in LazisMu Kebumen Regency.